IDENTIFIKASI CEDERA DAN UPAYA PENANGANAN CEDERA PADA AKTIVITAS PENDIDIKAN JASMANI DI SMP NEGERI 5 SEMARANG - Wicaksono, Thio Febrian; Supriyono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Injuries are a common risk in Physical Education, Sports, and Health classes due to high levels of physical activity. This situation requires sports teachers to be able to identify various types of injuries and provide appropriate care to minimize their impact. This study aims to describe the types of injuries occurring during sports lessons and the injury management efforts undertaken by sports teachers at SMP Negeri 5 Semarang. A qualitative, descriptive research approach was employed. Participants included sports teachers, first aid/school health unit staff, and 30 eighth-grade students selected via purposive sampling. Data were collected through interviews, observation, and documentation, and subsequently analyzed using data reduction, data presentation, and conclusion drawing. Data validity was verified through source and technique triangulation. The findings indicate that fainting and abrasions were the most common injuries, while others included bruises, muscle cramps, sprains, and fractures. Factors contributing to injuries included suboptimal student physical condition, insufficient food and fluid intake, the frequency of sports activities, field conditions, and hot weather. Injury management was carried out by sports teachers in collaboration with first aid/school health unit staff, involving first aid measures tailored to the specific type of injury. However, challenges remained, such as limited supervision, variations in students' physical conditions, and a lack of supporting facilities. Therefore, it is necessary to enhance teachers' first aid competence, provide adequate first aid facilities, and strengthen injury prevention programs to improve safety during sports lessons. Keywords: injury identification, injury management, physical education